Evaluating and Developing Transversal and Sustainability Competencies in University Classrooms to Empower New Generations. - Tójar-Hurtado, Juan-Carlos; Lechuga-Jiménez, Clotilde; Esteban Ibáñez, Macarena (MDPI, 2024)
This study examines the convergence of sustainability competencies in Spanish university curricula. The objective is to analyse and contrast opinions among university teaching staff and students from different fields of study in relation to the presence of competencies and curricular improvements concerning sustainability. The procedure comprised two surveys applied to professors (n2 = 70) and students (n3 = 698). The instrument employed was the Register for Evaluating Curricular Sustainability at the University (RECSU), which permits the collation of data pertaining to sustainability-related transversal competencies, including sustainability values, the use of sustainable methodology in the classroom, the Sustainable Development Goals, and principles of action. In its entirety, this study’s approach uses a mixed QUAN (qual) QUAL design. The results indicate which sustainability-aligned competencies and teaching practices are the most and least utilised by teaching staff, as well as which competencies present the greatest opportunity for improvement from the perspective of teaching staff. The findings highlight the relevance of empowering new generations through the development of transversal competencies in university studies. Sustainability competencies should be a priority to ensure that students are prepared to face future eco-social challenges.
Keywords: Investigación activa en educación; Higher education; Competencies; Transversality; Sustainability